Kala I Fase Aktif Multipara Dengan Apgar Skor - Siti Choirul Dwi Astuti; Rabia Zakaria (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
The APGAR score is a simple method used to assess the general condition of the baby immediately after birth. This assessment is necessary to determine asphyxia in newborns. The APGAR score is influenced by many factors, one of which is the duration of labor. For the longest time it takes for labor to be in the first stage. Maternal parity also determines the duration of the first stage. Monitoring of mothers in labor begins during the active phase of the first stage. The purpose of this study in general was to determine the effect of the first stage of the active multipara phase on the APGAR score. This research method is an observational posttest only control group design with a cross-sectional approach and uses a purposive sampling technique to determine 60 samples. Data analysis using ANOVA test. The results of this study showed a linear relationship between the first stage of the active phase and the APGAR score indicated by the p-value of 0.0001. In conclusion, the shorter the duration of the first stage of the active phase of multiparous APGAR mothers, the score will increase.